2012
DOI: 10.1128/iai.00331-12
|View full text |Cite
|
Sign up to set email alerts
|

FimA, FimF, and FimH Are Necessary for Assembly of Type 1 Fimbriae on Salmonella enterica Serovar Typhimurium

Abstract: ABSTRACTSalmonella entericaserovar Typhimurium is a Gram-negative member of the familyEnterobacteriaceaeand is a common cause of bacterial food poisoning in humans. The fimbrial appendages are found on the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…Choleraesuis was unable to produce type 1 fimbriae without FimH. This finding is in line with the report of Zeiner et al that indicated that FimA, FimF, and FimH are necessary for the assembly of type 1 fimbriae in Salmonella [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Choleraesuis was unable to produce type 1 fimbriae without FimH. This finding is in line with the report of Zeiner et al that indicated that FimA, FimF, and FimH are necessary for the assembly of type 1 fimbriae in Salmonella [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…The phenotypic expression of type 1 fimbriae is primarily a result of cooperation among several Fim proteins and arginine tRNA encoded by fimU within the fim gene cluster. FimA, FimI, FimH, and FimF are fimbrial subunits that form the shaft of type 1 fimbriae, with FimA as the major fimbrial subunit [ 7 ]. Type 1 fimbriae adhere to a variety of cells that possess mannose residues, such as erythrocytes, leukocytes, yeast, and respiratory cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another gene cluster that was ubiquitously present were the fim genes that encodes for type 1 fimbriae. This cluster is comprised of the fimAICDHF operon and three regulatory genes fimW, fimY, and fimZ and mediates adherence to eukaryotic cells [ 21 ]. However, the fimY gene was not detected in ten isolates at the BLAST search cut-off level we used.…”
Section: Resultsmentioning
confidence: 99%
“…The selection of an appropriate target gene for Salmonella detection is key to developing a great visualized LAMP method. Salmonella possesses many types of pili; type I pili are widely distributed among various serotypes, and the fimW gene is one of the major regulatory genes of type I pilus subunit proteins ( Supreet et al., 2009 , Zeiner et al., 2012 ). A search of sequences in GenBank using the fimW gene sequence as a query showed that fimW is a unique gene that is only present in different Salmonella serotypes, and no homologous sequences were found in other pathogens; therefore, we selected the fimW gene as an ideal target for the method.…”
Section: Discussionmentioning
confidence: 99%